GIS-based assessment of spatial and temporal disparities of urban health index in Shenzhen, China - Yongheng, Duan; Shan, Xie; Fei, Liu; Jinglin, Tang; Liyue, Gong; Xiaoying, Liu; Tingxiao, Wen; Hongrui, Wang (Frontiers in Public Health, 2024)
Purpose:To explore the inter-regional health index at the city level to contribute to the reduction of health inequalities.Employed the health determinant model to select indicators for the urban health index of Shenzhen City. Utilized principal component analysis, the weights of these indicators are determined to construct the said health index. Subsequently, the global Moran's index and local Moran's index are utilized to investigate the geographical spatial distribution of the urban health index across various administrative districts within Shenzhen.The level of urban health index in Shenzhen exhibits spatial clustering and demonstrates a